PENDEKATAN DESIGN FOR MANUFACTURE AND ASSEMBLY (DFMA) DAN HOUSE OF QUALITY (HoQ) UNTUK MERANCANG PALU MULTIFUNGSI - Wahyudi, Rizqi; Hermawan, Andre Aqshal; Nugraha, Andhyka Tyaz (Universitas PGRI Madiun, 2024)
The manufacturing industry has developed a lot both in the manufacturing and service industries. A very rapid and very dynamic development especially in the type of industry of irritating equipment and armoury. The development of tools began in 1775 by John Wilkinso who made the horizontal drill for the inner cylinder surface work. Nowadays a lot of new model tools are emerging that are required by distractions and disruptions. Examples are hammer and socket keys that are growing so rapidly and the industry is starting to keep competing to give innovation and advantages to its products so that it produces comfortable products and competitive prices. The aim of this study is to design a multifunctional hammer using the Design for Manufacturing and Assembly (DFMA) approach by looking at the conformity of product quality criteria based on the House of Quality (HoQ) as well as evaluating the prototype according to consumer criteria. Keywords: Tool design, hammer, socket wrenche, DFMA, and HOQ ABSTRAK Sektor industri manufaktur pada saat ini sudah mengalami kemajuan yang sangat signifikan baik di sektor industri manufaktur maupun jasa. Kemajuan yang sangat cepat dan sangat dinamis terutama pada jenis industri berupa peralatan perbengkelan dan pertukangan. Mulainya perkembangan perkakas diawali tahun 1775 oleh John Wilkinso yang membuat bor horizontal untuk pengerjaan permukaan silinder dalam. Saat ini banyak bermunculan perkakas model baru yang dibutuhkan oleh perbengkelan dan pertukangan. Sebagai contoh adalah palu dan kunci sok yang berkembang begitu pesatnya dan industri mulai terus bersaing memberikan inovasi dan keunggulan produknya sehingga menghasilkan produk yang nyaman dan harga yang bersaing. Tujuan dari penelitian ini adalah untuk merancang palu multifungsi dengan menggunakan pendekatan Design for Manufacturing and Assembly (DFMA) dengan melihat kesesuaian kriteria kualitas produk berdasarkan House of Quality (HoQ) serta mengevaluasi prototype sesuai dengan kriteria konsumen. Kata kunci: Perancangan alat, Palu, Kunci sok, DFMA, dan HoQ